Genetic Diversity and Population Structure Reveal Cryptic Genetic Variation and Long Distance Migration of Puccinia graminis f. sp. tritici in the Indian Subcontinent - Prasad, Pramod; Thakur, Rajni Kant; Savadi, Siddanna; Bhardwaj, Subhash Chander; Gangwar, Om Prakash; Lata, Charu; Adhikari, Sneha; Kumar, Subodh (Frontiers in Microbiology, 2022)
Stem rust caused by Puccinia graminis f. sp. tritici (Pgt) is a devastating disease of wheat worldwide since time immemorial. Several wheat stem rust outbreaks have been reported throughout the world including India. About 7 mha wheat area in central and peninsular India is highly vulnerable to stem rust epidemics. In this study, a repository of 29 single genotype uredospore pathotypes, representing five geographical regions were characterized by investigating their virulence phenotype and SSR genotypes using 37 reproducible polymorphic SSR markers, 32 of which had ≥0.50 PIC value. Virulence phenotypes were used to evaluate the virulence frequency (VF) and construct hypothetical evolutionary hierarchy of these pathotypes. We projected seven lineages to explain the evolutionary pattern of Pgt population. The VF of these pathotypes ranged between 0 to 100%. The virulence-based NJ cluster analysis grouped Pgt pathotypes into five virulence groups. Likewise, five molecular groups were categorized using molecular genotypes. The molecular grouping was supported by PCoA, which revealed 25% of the cumulative variance contributed by first two axes. AMOVA revealed 8% and 92% of the variation among and within the populations, respectively. The Mantel test confirmed a positive but weak correlation (R²=0.15) between virulence phenotypes and SSR genotypes. The highest and lowest values of different genetic diversity parameters (Na, Ne, I, He, uHe, and %P) revealed maximum and minimum variability in Pgt population from Maharashtra and Uttar Pradesh, respectively. The population structure analysis clustered 29 Pgt pathotypes into two sub-populations, and an admixture. Our results demonstrated that there was significant genetic diversity among Pgt pathotypes resulting from their long-distance dispersal ability complemented by gene flow. These findings provide insights into the virulence patterns, genetic variations, and possible evolution of Pgt pathotypes, which would support strategic stem rust resistance breeding.